On plant mites from Guadeloupe, with descriptions of four new species of Eriophyidae - Flechtmann, Carlos H.w.; Etienne, Jean (Zootaxa, 2005)
Seven species of plant mites are reported from Guadeloupe: two spider mites, Oligonychus biharensis (Hirst) and Tetranychus mexicanus (McGregor), Tetranychidae; one false spider mite, Brevipalpus phoenicis (Geijskes), Tenuipalpidae; two eriophyid mites, Colomerus bucidae (Nalepa) and Ectomerus triquetrus Flechtmann & Etienne, Eriophyidae; two phytoseiid mites, Amblyseius largoensis (Muma) and Iphiseiodes zuluagai Denmark & Muma, Phytoseiidae; and, four new species of eriophyid mites, namely Acalitus cracens n. sp. from Turnera subulata Smith (Turneraceae), Aceria doliolum n. sp. from Haematoxylon campechianum L. (Caesalpiniaceae), Eriophyes gallitor n. sp. from Sideroxylon obovatum (Lam.) (Sapotaceae) and Vasates caritus n. sp. from Haematoxylon campechianum L. (Caesalpiniaceae).